THE ROLE OF THE MUSLIM COMMUNITY IN COMBATING ISLAMOPHOBIA - Nasir Ali (Journal of Religion and Society, 2024)
Islamophobia, characterized by prejudice and hostility towards Islam and Muslims, has become a growing global challenge with significant social, economic, and psychological implications for Muslim communities worldwide. This article examines the proactive role that Muslim communities can play in combating Islamophobia through education, media engagement, interfaith dialogue, and legal advocacy. The study highlights the importance of promoting the true teachings of Islam, creating awareness campaigns, and fostering understanding among diverse communities. Furthermore, the paper explores successful examples of Muslim-led initiatives that have effectively countered Islamophobia, emphasizing the necessity of internal unity and collective effort. It also discusses the challenges faced by Muslim communities, including resource limitations and resistance to their efforts. The article concludes by providing actionable recommendations for enhancing the role of Muslim communities in addressing Islamophobia, promoting coexistence, and contributing to global peace and harmony. Keywords: Islamophobia, Muslim Community, Interfaith Dialogue, Media Representation, Social Justice, Religious Tolerance, Global Peace, Legal Advocacy.